Receding Horizon Adaptive Second-Order Sliding Mode Control for Doubly-Fed Induction Generator Based Wind Turbine - Evangelista, Carolina Alejandra (2017)
In this paper, a novel adaptive second-order sliding mode technique to optimize the efficiency of certain types of variable-speed wind turbines is developed and analyzed. A revisited form of a recent adaptation algorithm is proposed to deal with the characteristics and control requirements of wind energy conversion systems (WECS), particularly model uncertainties and fast disturbances due to gusty wind effects. The revisited algorithm is based on appropriate receding horizon adaptation time windows rather than on fixed, adjacent, and nonoverlapping ones. This modification, which enhances the reactivity of the adaptation strategy against fast varying uncertainties, represents the main theoretical novelty of this paper. The proposed approach is successfully used to control a doubly fed induction-generator-based wind turbine topology proving its suitability for this application area. The novel adaptive controller is extensively assessed through computer simulations over a full-order realistic model of the WECS under study.